2015
DOI: 10.1002/2015gc005733
|View full text |Cite
|
Sign up to set email alerts
|

The insular shelves of the Faial‐Pico Ridge (Azores archipelago): A morphological record of its evolution

Abstract: Shelves surrounding reefless volcanic ocean islands are formed by surf erosion of their slopes during changing sea levels. Posterosional lava flows, if abundant, can cross the coastal cliffs and fill partially or completely the accommodation space left by erosion. In this study, multibeam bathymetry, highresolution seismic reflection profiles, and sediment samples are used to characterize the morphology of the insular shelves adjacent to Pico Island. The data show offshore fresh lava flow morphologies, as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
79
1

Year Published

2016
2016
2017
2017

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 54 publications
(86 citation statements)
references
References 70 publications
(120 reference statements)
3
79
1
Order By: Relevance
“…Several authors consider that Faial and Pico are the emerged parts of a single main volcanic ridge, the Pico-Faial ridge (Hildenbrand et al, 2012 and references therein;Quartau et al, 2015). In the present study we will analyze the degassing patterns associated to each island individually.…”
Section: Tectonic Structures and Seismicitymentioning
confidence: 97%
“…Several authors consider that Faial and Pico are the emerged parts of a single main volcanic ridge, the Pico-Faial ridge (Hildenbrand et al, 2012 and references therein;Quartau et al, 2015). In the present study we will analyze the degassing patterns associated to each island individually.…”
Section: Tectonic Structures and Seismicitymentioning
confidence: 97%
“…In the opening of the Abstract of their paper, Quartau et al . [] state that “Shelves surrounding reefless volcanic ocean islands are formed by surf erosion of their slopes during changing sea levels.”; in the second paragraph of the Introduction they say that “The shelves surrounding volcanic ocean islands are formed by a competition between wave erosion, which forms and enlarges them, and volcanic progradation which narrows them”; and in section 4.1, dedicated to the conceptual model, they say that “The analysis of the data shows shelves that have been formed by wave erosion and whose accommodation space has been continually diminished by volcanic progradation, although some subsidence has occurred.” This means that, although recognizing the role of processes like subsidence, they actually did not estimate its rate, and consider mostly two dominant processes in their analysis: wave erosion and volcanic progradation. This might be true for stable islands (null vertical isostatic or tectonic movements), but not for subsiding islands as we argue in this comment.…”
Section: Commentmentioning
confidence: 99%
“…Quartau et al . [] concluded that “… insular shelves were formed by wave erosion of the flanks of the volcanic edifices of Faial and Pico Islands. Pico insular shelves have been significantly modified by later volcanic progradation,” thus not taking into proper account the major effects of large‐scale flank collapses in shaping a great part of Pico Island.…”
Section: Commentmentioning
confidence: 99%
See 2 more Smart Citations